2015
DOI: 10.1002/cncr.29640
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy versus no treatment for early stage non–small cell lung cancer in medically inoperable elderly patients: A National Cancer Data Base analysis

Abstract: BACKGROUND Stereotactic body radiation therapy (SBRT) has demonstrated high rates of local control with low morbidity and has now emerged as the standard of care for medically inoperable, early stage non–small cell lung cancer (NSCLC). However, the impact of lung SBRT on survival in the elderly population is less clear given competing comorbid conditions. An analysis of the National Cancer Data Base (NCDB) was undertaken to determine whether definitive SBRT improves survival relative to observation alone patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 27 publications
4
43
0
3
Order By: Relevance
“…Other retrospective literature examining lung SBRT in older patients includes a database analysis examining 3147 patients ≥70 years old where 96 of the 258 patients treated with SBRT were ≥80 years old. 27 The authors found that SBRT had improved OS versus observation (HR, 0.64). In a recent series by Mancini et al, examining 251 patients treated with lung SBRT, they dichotomized patients at age 75.…”
Section: Discussionmentioning
confidence: 98%
“…Other retrospective literature examining lung SBRT in older patients includes a database analysis examining 3147 patients ≥70 years old where 96 of the 258 patients treated with SBRT were ≥80 years old. 27 The authors found that SBRT had improved OS versus observation (HR, 0.64). In a recent series by Mancini et al, examining 251 patients treated with lung SBRT, they dichotomized patients at age 75.…”
Section: Discussionmentioning
confidence: 98%
“…The mean PTV of the FF and FFF groups was 50. 4 2), respectively. There were no significant differences between PTV and ITV (P=0.32, 0.64), respectively.…”
Section: Patientsmentioning
confidence: 99%
“…However, not all early-stage NSCLC patients are suited for surgery because of advanced age, patient refusal, or other reasons (3,4). Stereotactic body radiotherapy (SBRT) has been widely used as an effective alternative treatment for primary lung tumors, and reports excellent 3-year progression-free survival (PFS) of up to 90%, which is considerably better than past data with conventional radiotherapy (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Another report suggested that SBRT should be used for the treatment of elderly patients with early-stage NSCLC who are unable to tolerate surgical resection due to comorbid conditions. 21 Furthermore, recent study showed that the treatment outcomes of SBRT are not different from that of surgical operation in patients with stage I NSCLC. 22 Accordingly, SBRT can be a most relevant treatment for patients in stage I NSCLC.…”
Section: Discussionmentioning
confidence: 99%